Ileal Inflammation May Trigger the Development of GP2-Specific Pancreatic Autoantibodies in Patients with Crohn’s Disease - Polychronis Pavlidis; Ourania Romanidou; Dirk Roggenbuck; Maria G. Mytilinaiou; Faris Al-Sulttan; Christos Liaskos; Daniel S. Smyk; Andreas L. Koutsoumpas; Eirini I. Rigopoulou; Karsten Conrad; Alastair Forbes; Dimitrios P. Bogdanos (Clinical and Developmental Immunology, 2012)
Why zymogen glycoprotein 2 (GP2), the Crohn’s disease (CD)-specific pancreatic autoantigen, is the major target of humoral autoimmunity in inflammatory bowel diseases (IBD) is uknown. Recent evidence demonstrates that GP2 is also present on the apical surface of microfold (M) intestinal cells. As the colon lacks GP2-rich M cells, we assumed that patients with colonic CD are seronegative for anti-GP2. Anti-GP2 antibodies were tested in 225 CDs, including 45 patients with colonic location (L2), 45 with terminal ileum (L1) and 135 with ileocolonic involvement; 225 patients with ulcerative colitis (UC) were also tested. Anti-GP2 reactivity was detected in 59 (26.2%) CDs and 15 (6.7%) UCs (P<0.001). Only 5 CDs with L2 had anti-GP2 antibodies, compared to 54/180 (30.0%, P=0.0128) of the CDs with L1 and L3. Anti-GP2 antibody positive CD patients had higher ASCA titres compared to seronegative cases. Amongst the 128 CD patients with previous surgical intervention, 45 (35.0%) were anti-GP2 antibody positive compared to 14/97 (14.0%) without surgical (P<0.001). Our data support the assumption that ileal inflammation is required for the development of anti-GP2 antibodies in CD, and suggest that the intestine rather than the pancreatic juice is the antigenic source required for the initiation of anti-GP2 antibodies.